Tinjauan Skala Ukuran Perusahaan terhadap Perilaku Entrepreneurial Marketing serta kaitanya dengan Dominasi Dimensi Opportunity dan Growth Orientation - Christina Whidya Utami; Hendro Susanto (Jurnal Bisnis dan Keuangan, 2019)
This study aims to bridge the gap in the literature by examining the dimensions of Growth Orientation, Opportunity Orientation, Total customer focus dimensions, Value creation Networking, Informal Market Analysis, Closness to The Market on large and small company scale related to Entrepreneurial Marketing (EM) behavior. Thus the objectives to be developed in this study are: analyze how EM behavior in small companies compared to large companies? The dimensions of whether in entrepreneurial marketing are dominant in the context of small and large scale companies. The questionnaire was aimed at a national sample of 406 business owners in Indonesia, spread in 8 provinces. Small companies are defined as companies that employ at least 9 fewer full-time employees other than their owners, while large companies are companies that employ more than 9 full-time employees other than their owners. Snowball sampling is used to determine the selected respondent. The results showed that there are differences in entrepreneurial marketing behavior between large companies and small companies, where small scale companies have lower entrepreneurial marketing behavior compared to large scale companies. For small scale companies, it shows that opportunity orientation is the most dominant dimension, whereas in large scale companies it shows that growth orientation is the most dominant dimension.